Effect of crystal orientation on recrystallization occurrence in CMSX-4 - E. Hazemann; Y. Zhang; K. Inal; M. Long; N.-T. Niane; A.Pinto Mora; V. Maguin; M. Leduc; V. Jaquet; M. Bellet; Ch.-A. Gandin (Materials & Design)
An experimental study of recrystallized grains (RG) is carried out for the single crystal (SX) nickel-based superalloy CMSX-4 for both isothermal and non-isothermal tensile tests on specimens oriented alongh <100>, <110> and <111> crystallographic orientations. For the isothermal tensile tests coupled with relaxation cycles, a new normalized parameter is defined using the recrystallization length and the maximum strain along the loading direction, both measured for each specimen. It is used to discuss the sensitivity to the formation of RG as a function of temperature and crystal orientation. For the non-isothermal test, designed to represent typical thermomechanical history of SX parts during casting, no recrystallization is observed for <110> oriented specimens, while it is found for <100> and <111> orientations, with highest sensitivity for <100> orientation. These findings open the way to a new design of parts that are highly sensitive to the occurrence of RG. A recrystallization criterion is sketched based on the analysis of the experimental results.